2016
DOI: 10.1038/oncsis.2016.78
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional dissection of a context-dependent role for Hif1α in pancreatic tumorigenesis

Abstract: Hypoxia-inducible factor 1α (Hif1α) is a key regulator of cellular adaptation and survival under hypoxic conditions. In pancreatic ductal adenocarcinoma (PDAC), it has been recently shown that genetic ablation of Hif1α accelerates tumour development by promoting tumour-supportive inflammation in mice, questioning its role as the key downstream target of many oncogenic signals of PDAC. Likely, Hif1α has a context-dependent role in pancreatic tumorigenesis. To further analyse this, murine PDAC cell lines with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Previously, we characterized a highly metastatic mouse model of PDAC that was driven by one allele loss of tuberous sclerosis 1 together with pancreas-specific oncogenic Kras G12D expression ( p48 Cre ; Kras G12D/+ ; Tsc1 -/+ ). 18 , 19 , 20 A particular signature of "Mek/Erk-mTOR" was identified by using cancer cell lines from those animals. The Kyoto Encyclopedia of Genes and Genomes pathway analysis of this signature uncovered the glucose-related metabolism as the major enriched pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we characterized a highly metastatic mouse model of PDAC that was driven by one allele loss of tuberous sclerosis 1 together with pancreas-specific oncogenic Kras G12D expression ( p48 Cre ; Kras G12D/+ ; Tsc1 -/+ ). 18 , 19 , 20 A particular signature of "Mek/Erk-mTOR" was identified by using cancer cell lines from those animals. The Kyoto Encyclopedia of Genes and Genomes pathway analysis of this signature uncovered the glucose-related metabolism as the major enriched pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we generated a number of PDAC entities with different potency of aggressiveness by using a set of transgenic mouse models (5)(6)(7)(8)(9). Notably, in the context of Tsc1 haploinsufficiency, Kras G12D preferably activated mTOR signaling via the Mek/Erk cascade, contributing to a PDAC subtype with high-metastasis potential (8).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of molecular subtypes with distinctive tumor biology seem to exist (4), thus it is an unmet need to subclassify PDAC into clinically relevant subtypes and subsequently to develop targeted therapies accordingly. In this regard, we previously used a reverse-translational approach to define PDAC subtypes in mice (5)(6)(7)(8)(9) and generated several novel transgenic mouse models of PDAC entities with different potency of aggressiveness. Detailed analyses revealed that metastasis was driven by the Kras G12D /Mek/mTOR signaling axis, for which ALDH1A3 (aldehyde dehydrogenase family 1, subfamily A3) constituted a specific marker (8).…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1 activity in tumors depends on availability of the HIF-1a subunit, the levels of which increase under hypoxic conditions and through activation of oncogenes and/or inactivation of tumor suppressor genes. HIF1α 6 , 7 is required for hypoxia-induced cell cycle arrest, the mechanism that the enhancing stability of HIF-1α protein regulated cyclinD1 expression under hypoxia condition. HIF-1α 8 induced G0/G1 phase arrest may account for the resistance of cancer cells to some certain chemotherapeutic agents that target DNA synthesis in S phase.…”
Section: Introductionmentioning
confidence: 99%